Liver function tests to predict the severity of dengue fever in serologically positive children below 18 years of age - H. N., Yashwanth Raju; Kumar, Rajendra; Rudrappa, Sudha (International Journal of Contemporary Pediatrics, 2019)
Background: Dengue fever presents with a diverse clinical spectrum. Although liver is not a major target organ, hepatic dysfunction is a well-recognized feature. In this study authors attempted to study the pattern of hepatic involvement in children with dengue and its association with disease severity. Methods: This was a cross sectional study conducted at Cheluvamba hospital during the period of 1 year. Children <18 years of age with dengue Ns1 Ag and IgM positive were included in this study. After obtaining informed consent, a pre-structured proforma was used to record the relevant information from each subject. After detailed clinical examination and haematological investigation children were categorized into three groups as dengue fever with no warning signs (DNWS), dengue fever with warning signs (DWWS) and severe dengue fever (SDF) according to WHO classification. Statistical analysis was done to know the strength of association between different clinical and biochemical variables and outcome of the disease. Results: The mean age of the study population was 8.65 years with male preponderance. The mean total bilirubin, serum albumin, SGOT, SGPT, ALP, PT and INR were 0.76 mg/dl, 3.8g/dl, 233.18U/L, 118.15U/L, 200.65 U/L, 12.9s and 1.09 respectively. The mean SGOT was significantly higher than SGPT. The degree of deranged LFTs was significantly more in SDF group than DNWS and DWWS groups. Serum albumin was significantly decreased in children with SDF group correlating with disease severity, prognosis and outcome. Conclusions: Hepatic dysfunction was present in all forms of dengue infection, with SGOT rising significantly more than SGPT. All biochemical liver parameters were significantly deranged in patients with severe dengue fever indicating prolonged illness and poor prognosis.